Assessment of the complex system condition (on the example of an it сompany) - Goloskokov, Alexander; Yakovenko, Artem Anatolievich (Національний технічний університет "Харківський політехнічний інститут", 2019)
The paper considers the problem of estimating the state of the enterprise (on example of the IT company). The problem is presented in the form of two problems. The first problem is the aggregation of the initial information and the second problem is the identification of the state of a complex system. Authors formulated the problem and selected methods for solution of the problem. It is possible to form software for solving research problems.To solve the problem of aggregation of initial data authors used the fuzzy cluster analysis, namely the fuzzy k-means method. A numerical research was carried out and a test case was figured out in the MATLAB environment. In this test case the source data was reduced to a dimensionless form. Thereafter, already reduced to the same scale, the initial attributes were reduced to fuzziness. The results allow to formalize linguistic variables, whi ch are characterized by the term-sets and definition range. The numerical results were approximated by analytical membership functi ons. The solution of the first task allows to generate a set of possible fuzzy reference situations, which reflect the possible state of the system. E ach situation is characterized by the reference informational granule, which contains information about formalized linguistic variables. The second problem was solved by using the method of fuzzy logic in the MATLAB environment. The test case was calculated. In this test case, the search of the situation in which the IT-company is located was performed. At this stage, the current situation belongs to comparison with each reference situation. In this way, authors determined the most similar reference situation to the current situation. An analysis of the resulting situation allows to argue the state of the IT company. The solution of the second task allowed to establish assessment of IT company state. The theoretical and practical results can improve the efficiency of complex system management.

У роботі розглянута проблема оцінки стану підприємства (на прикладі IT-компанії). Проблема представлена у вигляді двох задач, а саме: агрегування вихідної інформації і ідентифікація стану складної системи. Сформульовано постановки задачі та обрані методи їх вирішення. Це дозволило сформувати математичне забезпечення для вирішення задачі дослідження. Для вирішення задачі агрегування вхідних даних використаний нечіткий кластерний аналіз, а саме нечіткий метод К-середніх. Здійснено числові дослідження та прорахований тестовий приклад в середовищі MATLAB. В рамках даного тестового прикладу здійснено приведення вхідних даних до безрозмірного вигляду. Після цього, вже приведені до єдиної шкали, вхідні ознаки були приведені до нечіткості в результаті чого вдалося формалізувати лінгвістичні змінні, які характеризуються терм-множинами і областями визначення. Отриманий чисельний результат був апроксимований аналітичними функціями належності. Вирішення першого завдання дозволило сформувати множину можливих нечітких еталонних ситуацій, що відображають можливі стани системи. Кожна еталонна ситуація характеризується інформаційної гранулою, яка містить інформацію про формалізовані лінгвістичні змінні. Друга задача була вирішена за допомогою методу нечіткої логіки в середовищі MATLAB. Прорахований тестовий приклад, який полягає в пошуку ситуації, в якій знаходиться IT-компанія. На даному етапі поточна ситуація підлягає порівнянню з кожною еталонною ситуацією, в результаті чого визначається найбільш схожа ситуація до поточної. В результаті аналізу отриманої ситуації здійснюється аргументування стану IT-компанії. Вирішення другої задачі дозволило встановити оцінку стану IT-компанії. Отримані теоретичні та практичні результати дозволяють підвищити ефективність процесу управління складною системою.
Оцінка стану складних систем (на прикладі it-компанії)
Keywords: complex system management; condition assessment; fuzzy cluster analysis; situational approach; reference situations; informational granule; управління складною системою; оцінка стану об’єкту; нечіткий кластерний аналіз; нечіткий ситуаційний підхід; еталонні ситуації; інформаційна гранула